Treatment of Patients with Factor VIII and Factor IX Inhibitors with Special Focus on the Use of Recombinant Factor VIIa - Hedner, Ulla (Thrombosis and Haemostasis, 1999)
In caring for patients with hemophilia, the development of inhibitors against the missing coagulation protein remains a significant problem. Such inhibitors occur in about 15% of patients with severe hemophilia1 and are directed against the procoagulant part of the factor VIII or factor IX molecules. The goal in the treatment of patients with hemophilia is to achieve high enough levels of the missing factor to induce hemostasis in case of bleeding or to prevent bleeding during surgery. Patients with a low inhibitor titer, and especially those with a low anamnestic response, can be given high doses of the coagulation factor concentrate to induce hemostasis. However, for patients with high inhibitor levels, or high-responders, other treatments must be used, including procedures to decrease the antibody titers. To minimize the booster effect of high doses of antigen, immunosuppressive treatment may be added. Because such treatment procedures are complicated and associated with a number of potential side effects, they are not often used to treat mild-to-moderate bleeding episodes or to cover elective, less urgent surgery for inhibitor patients. As a result, a great deal of effort has been devoted to finding more convenient treatment modalities and to inducing immunologic tolerance to permanently eradicate the inhibitors.